Participants’ Experiences of a Workplace-Oriented Problem Gambling Prevention Program for Managers and HR Officers: A Qualitative Study - Rafi, Jonas; Ivanova, Ekaterina; Rozental, Alexander; Lindfors, Petra; Carlbring, Per (Frontiers in Psychology, 2019)
Workplace health promotion programs (WHPPs) refer to a set of health promotion and protection strategies implemented at a worksite and designed to meet the health and safety needs of employees. One important question for WHPPs is how middle management experience their participation in a WHPP. This study aims to explore this question further by applying a qualitative content analysis to interviews with thirteen managers and ten human resource officers participating in a WHPP focusing on problem gambling. The WHPP consisted of two components: policy implementation and skills-development training. The participants were interviewed about their experiences of these two components and the implementation process. The qualitative content analysis resulted in six themes: (1) Expectations of the skills-development training, (2) Experiences of and prior beliefs about problem gambling, (3) A good foundation, (4) The difficult conversation, (5) Appreciated aspects of the training sessions, and (6) Remaining obstacles. The results suggest that the presentation of cases, facts, and general knowledge was appreciated by most participants. However, participants also expressed that they would benefit from tailored interventions, more support in the policy implementation process, and following up on the results.